Multiple dimensions of university teacher self-concept - Construct validation and the influence of students' evaluations of teaching - Roche, L; Marsh, H (2000)
Despite the recognised importance of positive self-concepts in many settings, surprisingly little attention has been paid to teacher self-concepts - teachers' self-perceptions of their own teaching effectiveness. We integrate research literatures on self-concept and on students' evaluations of teaching effectiveness (SETs), develop a multidimensional university teacher self-concept instrument, and evaluate its psychometric properties (factor structure, reliability, validity). A multitrait-multimethod analysis of relations between multiple dimensions of teacher self-concept and corresponding SET rating dimensions provides good support for the construct validity of teacher self-concept responses. In support of a priori hypotheses based on self-concept theory, agreement between teacher self-concepts and SETs was moderate (median r = 0.20) for teachers who had not previously received SET feedback, but substantially higher (median r = 0.40) for teachers who had previously received SET feedback. Implications for further research on teacher self-reflection and for improving teaching effectiveness in higher education are discussed.